The Gross, Fine, and Oral Motor Functions in a Patient with Megalencephalic Leukoencephalopathy with Subcortical Cyst A Case Report: Motor functions in a Megalencephalic Leukoencephalopathy with Subcortical Cyst patient - sabermoghadam, reihane; Toktam Maleki Shahmahmood; Pooria Sarvghadi; Mehran Beiraghi Toosi (Iranian Journal of Child Neurology, 2023)
Megalencephalic Leukoencephalopathy with Subcortical Cysts (MLC) is a rare autosomal recessive neurodegenerative disorder. As motor deficits are a core feature of MLC, we reported on the gross, fine and oral motor functions in a MLC1 patient. Our patient demonstrated macrocephaly, deterioration of motor functions with ataxia, spasticity and intellectual disability. In addition to medical interventions, the patient received rehabilitation interventions of occupational therapy and speech therapy. Brain structures were analyzed with magnitude resonance imaging (MRI), and gross, fine and oral motor functions were analyzed with Gross Motor Function Measurement (GMFM), Purdue Pegboard Test (PPT) and Oral Motor Assessment Scale (OMAS) at age 2, as well as after interventions at age 5. The results showed that although the motor functions did improve due to the interventions, the patient still had weaknesses in gross, fine and oral motor functions when compared to his peers. These findings emphasize the importance of early referral for rehabilitation of motor function in order to increase their independence, participation in daily life and quality of life.